Extraction of ferum from coal bottom ash using acid soluble and ion exchange leaching method - Kamal N.M.; Itam Z.; Syamsir A.; Beddu S.; Muhammad D.; Latif A.F.A.; Hamid Z.A.A.; Razak N.A. (American Institute of Physics Inc., 2023)
Coal Bottom Ash (CBA) is a solid residue produced by coal-fired power plants. In Malaysia, seven power plants under Tenaga Nasional Malaysia continuously produce around 790 tons of CBA per day. Research found that CBA is composed of Ferric Oxide (Fe2O), Aluminum Oxide (Al2O), Calcium Oxide (Ca2O), and Sulphur Trioxide (SO3) in form of insoluble metal oxides. Many of these metals and their oxides are environmentally hazardous. When the CBA is disposed in landfills, the metal oxides are leached out and find their way into potable water and into animal and plantations. Disposal of the unused CBA is costly and poses financial disadvantages to power station and to the environment. However, the metals contained inside the CBA may be valuable to various industry if there is a way to extract the metals out of the CBA. By using the Acid Soluble (AS) and Ion Exchangeable (IE) methods, it was shown that Ferum could be effectively extracted by using Ion Exchangeable (IE) method compared to Acid Soluble (AS) by using citric acid. 2018 Author(s).